Enhanced oxygen evolution reaction activity of NiFe layered double hydroxide on nickel foam- reduced graphene oxide interfaces. (28th January 2019) - Li, Chenchen; Chen, Jun; Wu, Yu; Cao, Weiyi; Sang, Shangbin; Wu, Qiumei; Liu, Hongtao; Liu, Kaiyu
Abstract: Herein, we prepared a novel nickel iron-layered double hydroxide/reduced graphene oxide/nickel foam (NiFe-LDH/RGO/NF) electrodes by two step electrodeposition processes for oxygen evolution reaction (OER). The modification of NF by RGO increased the interface conductivity and electrochemical active surface areas (ECSA) of the electrode. The NiFe-LDH/RGO/NF electrode has shown higher catalytic activity with a lower overpotential of 150 mV at the current density of 10 mA cm −2 . The NiFe-LDH/RGO/NF electrode has also shown a small Tafel slope of 35 mV per decade due to the synergy effect between the larger ECSA and the conductive RGO interface. Furthermore, the electrodes exhibits almost 10 h stability under a general current density of 10 mA cm −2 . Highlights: The RGO/NF interface is prepared by a simple electrodeposition method. The RGO/NF interface significantly increased the electrochemical activity of NiFe-LDH. NiFe-LDH/RGO/NF electrode far outperforms IrO2 catalyst in activity and kinetics.